Womanist Midrash Volume 2 A reintroduction to the women of Joshua, Judges, Samuel, and Kings - Gafney, Wilda 1966- (Louisville, Kentucky Westminster John Knox Press, 2024)
Continues Gafney's unique and imaginative work of in-depth translation-based explorations of the well- and lesser-known women and girls of the Hebrew Scriptures. This volume focuses on the women in the books of Joshua, Judges, Samuel, and Kings-- Provided by publisher
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Feminist criticism; Women in the Bible; Womanism -- Religious aspects -- Judaism; Womanist Theology